Pengaruh full day school terhadap perkembangan psikologi anak: Studi di smpit luqman al hakim slawi, kabupaten tegal - Nukhbatun Nisa; Muhamad Yusuf Amin Nugroho; Aryadi Nursantsoso (Piramida Akademi, 2026)
The policy of the full-day school system in Indonesia has a strong relevance to the psychological well-being of children. This study aimed to determine the effect of the Full Day School system on children's psychological development at SMPIT Luqman Al-Hakim Slawi, Tegal Regency. This research used a quantitative approach with a field research design. The population of this study consisted of all students, with a sample of eighth-grade students selected using a simple random sampling technique. Data collection techniques included questionnaires, observation, and documentation, while data analysis was conducted using normality test, linearity test, descriptive analysis, Pearson Product Moment correlation, simple linear regression, t-test, and coefficient of determination. The results showed that the Full Day School variable was in the good category with a percentage of 79.65% and children's psychological development was also in the good category with a percentage of 78.51%. There was a positive effect between Full Day School and children's psychological development with a correlation value of 0.574, which is categorized as moderate. The hypothesis test showed that the t-value of 6.902 was greater than the t-table value of 1.984, indicating a significant effect. In addition, the contribution of Full Day School to children's psychological development was 32.9%. Thus, the Full Day School system has a positive and significant effect on children's psychological development. Keywords: Full Day School; psychological development; education. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh sistem Full Day School terhadap perkembangan psikologi anak di SMPIT Luqman Al Hakim Slawi Kabupaten Tegal. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian lapangan. Populasi penelitian adalah seluruh siswa, dengan sampel siswa kelas VIII yang dipilih menggunakan teknik simple random sampling. Teknik pengumpulan data menggunakan angket, observasi, dan dokumentasi, sedangkan analisis data dilakukan melalui uji normalitas, uji linearitas, analisis deskriptif, korelasi Pearson Product Moment, regresi linear sederhana, uji t, dan koefisien determinasi. Hasil penelitian menunjukkan bahwa penerapan Full Day School berada pada kategori baik dengan persentase sebesar 79,65% dan perkembangan psikologi anak juga berada pada kategori baik dengan persentase sebesar 78,51%. Terdapat hubungan positif antara Full Day School dan perkembangan psikologi anak dengan nilai korelasi sebesar 0,574 yang termasuk dalam kategori sedang. Hasil uji hipotesis menunjukkan bahwa nilai t hitung sebesar 6,902 lebih besar dari t tabel 1,984 sehingga terdapat pengaruh yang signifikan. Selain itu, kontribusi Full Day School terhadap perkembangan psikologi anak sebesar 32,9%. Dengan demikian, sistem Full Day School berpengaruh positif dan signifikan terhadap perkembangan psikologi anak.